2007
DOI: 10.1097/fpc.0b013e3280d5121c
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in TP53, nonsteroidal anti-inflammatory drugs and the risk of colorectal cancer: evidence for gene–environment interaction?

Abstract: These data suggest that the TP53 genotype may modify the influence of nonsteroidal anti-inflammatory drug use on the risk of colorectal cancer. A direct proof of functional analysis is warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
4
27
1
Order By: Relevance
“…A few studies mentioned earlier also investigated haplotypes based on the TP53 polymorphisms, mainly including rs17878362:A 1 4A 2 and rs1042522:G4C [Perfumo et al, 2006;Tan et al, 2007], but also MspI RFLPs in intron 6 [Sjalander et al, 1995]. The earlier data have been inconsistent; however, Tan et al [2007], in agreement with our results, reported a significantly differential distribution of the haplotypes based on the rs17878362:A 1 4A 2 and rs1042522:G4C polymorphisms between CRC cases and controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A few studies mentioned earlier also investigated haplotypes based on the TP53 polymorphisms, mainly including rs17878362:A 1 4A 2 and rs1042522:G4C [Perfumo et al, 2006;Tan et al, 2007], but also MspI RFLPs in intron 6 [Sjalander et al, 1995]. The earlier data have been inconsistent; however, Tan et al [2007], in agreement with our results, reported a significantly differential distribution of the haplotypes based on the rs17878362:A 1 4A 2 and rs1042522:G4C polymorphisms between CRC cases and controls.…”
Section: Discussionsupporting
confidence: 92%
“…Other recent studies on TP53 rs1042522:G4C, on relatively small populations, have reported an association of the C allele with increased CRC risk [Goodman et al, 2006;Pérez et al, 2006;Zhu et al, 2007;Dakouras et al, 2008;Mammano et al, 2008]. Two larger and well-designed studies [Koushik et al, 2006;Tan et al, 2007] have reported discordant results. The first study did not find any association between the TP53 rs1042522:G4C polymorphism and CRC risk, but a moderate association with risk of adenoma due to the C allele.…”
Section: Discussionmentioning
confidence: 88%
“…For breast cancer, for example, results vary from protective [9][10][11][12] to no association [13][14][15] or increase in risk. [16][17][18] Similar conflicting results are also observed for esophageal, [19][20][21][22] lung, [23][24][25] and colorectal cancer [26][27][28] and other cancer types. To better understand the role of Arg72-Pro, recent meta-analysis studies have been performed for different cancer types, such as lung, 29 gastric, 30 and cervical cancer.…”
mentioning
confidence: 79%
“…Inaddition,thefactthatpublishedstudieshavebeenconductedonvariousChinese [11,16,21,[25][26][27],Caucasian [7,8,10,[12][13][14][15][17][18][19][20]22,24,[28][29][30][31][32][33]andmixed [9,23]populations renders the field even more challenging; indeed, our metaanalytical algorithm has revealed that race-specific effects often arise in meta-analyses concerning the association betweencancerriskandgeneticpolymorphisms [34][35][36][37][38][39][40].Specifically, concerning p53 Arg72Pro, the modulating effects of race have been demonstrated in various cancer types at a meta-analyticallevel.Inbreastcancer,theprotectiveeffectof the Pro allele was confined to European populations [3]; on thecontrary,theprotectiveeffectoftheArgallelewasconfinedtoAsiansubjectsingastriccancer [5].Asaresult,the in-depth examination of the association between p53 Arg72Propolymorphismstatusandcancerriskessentiallyencom-passestheevaluationofrace-specificeffects.…”
Section: Introductionmentioning
confidence: 99%